Laparoscopic extirpation of an intra-abdominal compressed air firearm pellet in a grownup: a rare case report - Prasanth Raveendran Rani, Arun; Nayar, Prathapan V.; Xavier, Bichu; Manohar, Balaji (International Surgery Journal, 2019)
With expanded automation of life, abdomino-thoracic wounds have progressively gone in a new direction. Penetrating wounds would now be able to be brought about by inadvertent impaction of directed items joined toward machines or different structures. Emergency health care professionals frequently belittle the potential for pellet and ball bearing firearms to incur dangerous penetrating wounds. Here we will talk about a 37 year elderly person arrived in emergency division with grievances of unintentional pellet (air gun) damage to the abdomen. He then underwent extirpation of compressed air firearm pellet laparoscopically around the same time and sent home on the third day after complete recuperation. We further examine about the compressed air firearm related wounds.